2018
DOI: 10.1302/1863-2548.12.180037
|View full text |Cite
|
Sign up to set email alerts
|

Stomaching the pain of spinal fusion: Gastrointestinal discomfort is as severe as back pain in 50% of adolescent idiopathic scoliosis patients following posterior spinal fusion

Abstract: Abstract:PurposeThere have been no prospective studies investigating gastrointestinal (GI) symptoms of patients with adolescent idiopathic scoliosis (AIS) following posterior spinal fusion (PSF). The purpose of this study was to evaluate the incidence and severity of self-reported GI symptoms following PSF.MethodsIn all, 40 AIS patients undergoing PSF were prospectively enrolled between March 2015 and October 2016. Patients completed a survey on each postoperative, inpatient day regarding nausea, emesis, const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…A study of patient reported postoperative GI symptoms found that half of patients selfreported that their abdominal pain and discomfort was equivalent in severity to their back pain following PSF, and that overall incidence of GI issues following PSF was high, occurring in over half (65%) of all participants. 4 The use of methylnaltrexone has the potential to reduce constipation and subsequent GI discomfort and pain, which may lead to overall improvement in postoperative pain experienced by patients undergoing PSF. While pain control regimens are often focused on controlling back pain, the potential to reduce GI related discomfort is critical for overall patient postoperative experiences.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A study of patient reported postoperative GI symptoms found that half of patients selfreported that their abdominal pain and discomfort was equivalent in severity to their back pain following PSF, and that overall incidence of GI issues following PSF was high, occurring in over half (65%) of all participants. 4 The use of methylnaltrexone has the potential to reduce constipation and subsequent GI discomfort and pain, which may lead to overall improvement in postoperative pain experienced by patients undergoing PSF. While pain control regimens are often focused on controlling back pain, the potential to reduce GI related discomfort is critical for overall patient postoperative experiences.…”
Section: Discussionmentioning
confidence: 99%
“…3 The incidence of postoperative gastrointestinal (GI) issues following PSF is high, with 1 study finding that over half of AIS patients self-reported abdominal symptoms and frequently rated them as severe as their back pain. 4 There are multiple contributing factors leading to GI symptoms, particularly constipation, following spinal surgery. A significant cause is the use of opiates for pain control, which can result in opioid-induced constipation (OIC).…”
mentioning
confidence: 99%
See 3 more Smart Citations